Comparative systems toxicology analysis of cigarette smoke and aerosol from a candidate modified risk tobacco product in organotypic human gingival epithelial cultures: A 3-day repeated exposure study. (March 2017) - Zanetti, Filippo; Titz, Bjoern; Sewer, Alain; Lo Sasso, Giuseppe; Scotti, Elena; Schlage, Walter K.; Mathis, Carole; Leroy, Patrice; Majeed, Shoaib; Torres, Laura Ortega; Keppler, Brian R.; Elamin, Ashraf; et al.
Abstract: Smoking is one of the major lifestyle-related risk factors for periodontal diseases. Modified risk tobacco products (MRTP) offer a promising alternative in the harm reduction strategy for adult smokers unable to quit. Using a systems toxicology approach, we investigated and compared the exposure effects of a reference cigarette (3R4F) and a heat-not-burn technology-based candidate MRTP, the Tobacco Heating System (THS) 2.2. Human gingival epithelial organotypic cultures were repeatedly exposed (3 days) for 28 min at two matching concentrations of cigarette smoke (CS) or THS2.2 aerosol. Results showed only minor histopathological alterations and minimal cytotoxicity upon THS2.2 aerosol exposure compared to CS (1% for THS2.2 aerosol vs. 30% for CS, at the high concentration). Among the 14 proinflammatory mediators analyzed, only 5 exhibited significant alterations with THS2.2 exposure compared with 11 upon CS exposure. Transcriptomic and metabolomic analysis indicated a general reduction of the impact in THS2.2 aerosol-exposed samples with respect to CS (∼79% lower biological impact for the high THS2.2 aerosol concentration compared to CS, and 13 metabolites significantly perturbed for THS2.2 vs. 181 for CS). This study indicates that exposure to THS2.2 aerosol had a lower impact on the pathophysiology of human gingival organotypic cultures than CS. Graphical abstract: Highlights: Systems toxicology approach to compare the effects of cigarette smoke and THS2.2 aerosol on gingival organotypic cultures. Organotypic gingival cultures resemble the native gingival epithelium in the response to cigarette smoke. Oxidative stress, xenobiotic metabolism and inflammation gene networks are perturbed by cigarette smoke. THS2.2 aerosol has a reduced impact on gingival organotypic cultures compared to cigarette smoke.